Pengaruh Keunikan Proses Produksi Arak Bali dan Promosi Terhadap Niat Berkunjung Dan Partisipasi Promosi Oleh Konsumen Pada Rumah Makan Dapoer Bali Mula di Desa Les, Kecamatan Tejakula, Buleleng - Widuri, Setyowati Ayu; Arcana, I Nyoman; Juniari , Ni Kadek Eni Juniari; Saputra, I Nyoman Gede Agus Jaya; Rusdiarnata, I Ketut (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2025)
Dapoer Bali Mula restaurant in Les Village, Tejakula District, Buleleng offers educational tour packages on the preservation of Balinese Arak and traditional Balinese dishes for tourists. This study aims to determine the influence of the uniqueness of the Balinese Arak production process and promotion on the participation of consumers with the intention to visit as an intervening variable in the Dapoer Bali Mula restaurant with 108 respondents. The statistical analysis used in this study is Path Analysis. The results of the study show that: 1) The uniqueness of the Balinese Arak production process and promotion affects the intention to visit; 2) The intention to visit, the uniqueness of the Balinese Arak production process and promotion affect the participation of consumers in promotion, both on their social media accounts and through